Characterisation of novel TLR-dependent immunomodulators from tropical plant extracts - Thirlaway, Khalil (2018)
Toll-like receptors (TLRs) recognise a wide range of molecular patterns, and are key in activation and coordination of the innate and adaptive immune responses. TLR ligands include pathogen-associated and damage-associated molecular patterns (PAMPs and DAMPs, respectively), as well as an increasing number of plant-derived ligands. Novel TLR ligands represent promising potential therapeutics, for example as vaccine adjuvants or selectively immunosuppressive drugs.